Pengaruh Hubungan Corporate Governance Terhadap Kinerja Keuangan - Yudha Prawira; Haryanto Haryanto (Diponegoro Journal of Accounting, 2015)
This   study   examined   the   relationship   of   the   Effect   of   Corporate Governance   Financial  Performance   Against  a  case  study  on  the  financial company 'listed on the Stock Exchange in 2010-2012. The purpose of this study was to determine the effect of board size, the size of the independent directors, the size of the board of directors, managerial ownership on firm performance.The population  in this study were all financial  companies listed on the Jakarta Stock Exchange (JSX) during the study period, ie 2010-2012. The sample in this study sample of 198 companies.The  results  showed  that  the  composition  of  the  independent  directors (having  a positive  influence  on the performance  of the company,  the effect of board size positively on the performance  of the company,  the effect size of the board   of  directors   is  positively   significant   to  the  company's   performance managerial ownership has a negative effect on the performance of the company.